Enterprise integration framework and semantic metadata in financial industry. (15th January 2008) - Wu, Raymond
This paper aims the enterprise architecture issue as a means of addressing the vertical gap in the cross-layers interconnectivity. We launched framework to address the integration strategy of metadata integration between business, service and information layers. This creates vertical alignment and uses metadata configuration to construct the mapping between each layer. This research paper reviews component-based implementation and uses an example in financial industry to review the design process from micro-component design to macro-component-based service virtualisation. The supplementary solutions of these two processes construct the enterprise integration interoperability and service virtualisation, which is the priority in financial industry.